Financial Depth as a Method to Reduce Financial Fragility - Ahmed Abbas Hussein; Alaa Abdulsalam Mustafa; Rasool Majid Sahaib (Scholars Digest Publishing, 2023)
The study aims to determine the general direction that the indicators of financial depth in Iraqi banks and the level of financial fragility in Iraqi banks can take. The study assumes that there are upward trends in the indicators of financial depth and the variation in the ratio and trend of financial depth in Iraqi banks during the study period. The study showed that Iraqi banks are exposed to banking fragility as a result of a number of factors, including internal factors related to the bank and other external ones, such as the economic, political and security conditions. The study recommends that Iraqi banks develop efficient and effective diversification strategies for financing sources between owned financing and borrowed financing in order to achieve an optimal mix between them, which makes financing costs to a minimum.
Keywords: Financial depth; financial fragility; Iraqi banks.